Using and choosing digital health technologies: a communications science perspective. Issue 1 (20th March 2017) - Ovretveit, John; Wu, Albert; Street, Richard; Thimbleby, Harold; Thilo, Friederike; Hannawa, Annegret
Abstract : Purpose: The purpose of this paper is to explore a non-technical overview for leaders and researchers about how to use a communications perspective to better assess, design and use digital health technologies (DHTs) to improve healthcare performance and to encourage more research into implementation and use of these technologies. Design/methodology/approach: Narrative overview, showing through examples the issues and benefits of introducing DHTs for healthcare performance and the insights that communications science brings to their design and use. Findings: Communications research has revealed the many ways in which people communicate in non-verbal ways, and how this can be lost or degraded in digitally mediated forms. These losses are often not recognized, can increase risks to patients and reduce staff satisfaction. Yet digital technologies also contribute to improving healthcare performance and staff morale if skillfully designed and implemented. Research limitations/implications: Researchers are provided with an introduction to the limitations of the research and to how communications science can contribute to a multidisciplinary research approach to evaluating and assisting the implementation of these technologies to improve healthcare performance. Practical implications: Using this overview, managers are more able to ask questions about how the new DHTs will affect healthcare and take a stronger role in implementing these technologies to improve performance. Originality/value: New insights into the use and understanding of DHTs from applying the new multidiscipline of communications science. A situated communications perspective helps to assess how a new technology can complement rather than degrade professional relationships and how safer implementation and use of these technologies can be devised.